Auditory Mismatch Negativity in Response to Changes of Counter-Balanced Interaural Time and Level Differences - Altmann, Christian F.; Ueda, Ryuhei; Furukawa, Shigeto; Kashino, Makio; Mima, Tatsuya; Fukuyama, Hidenao (Frontiers in Neuroscience, 2017)
Interaural time differences (ITD) and interaural level differences (ILD) both signal horizontal sound source location. To achieve a unified percept of our acoustic environment, these two cues require integration. In the present study, we tested this integration of ITD and ILD with electroencephalography (EEG) by measuring the mismatch negativity (MMN). The MMN can arise in response to spatial changes and is at least partly generated in auditory cortex. In our study, we aimed at testing for an MMN in response to stimuli with counter-balanced ITD/ILD cues. To this end, we employed a roving oddball paradigm with alternating sound sequences in two types of blocks: a) lateralized stimuli with congruently combined ITD/ILD cues and b) midline stimuli created by counter-balanced, incongruently combined ITD/ILD cues. We observed a significant MMN peaking at about 112-128 ms after change onset for the congruent ITD/ILD cues, for both lower (0.5 kHz) and higher carrier frequency (4 kHz). More importantly, we also observed significant MMN peaking at about 129 ms for incongruently combined ITD/ILD cues, but this effect was only detectable in the lower frequency range (0.5 kHz). There were no significant differences of the MMN responses for the two types of cue combinations (congruent/incongruent). These results suggest that – at least in the lower frequency ranges (0.5 kHz) – ITD and ILD are processed independently at the level of the MMN in auditory cortex.